Status Hukum Peraturan Pimpinan Badan Layanan Umum (BLU) yang Dikecualikan dalam Ketentuan Pengadaan Barang dan Jasa - Abd. Wafi; Ansori Ansori; Mukhlis Mukhlis (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The status of Public Service Agency (PSA) leadership regulations that are exempted from provisions on the procurement of goods and services. The main focus of this study is to examine the legal position of PSA internal regulations, particularly rector regulations within State Public Service Agency Universities (PTN BLU), and their impact on the implementation of goods and services procurement (PBJ). The problem arises because BLU internal regulations are often used as the basis for PBJ implementation, even though they are not recognized hierarchically in Law Number 12 of 2011 concerning the Formation of Legislation. This creates the potential for a conflict of norms with Presidential Regulation No. 16 of 2018 concerning PBJ and its derivative regulations, which can lead to legal uncertainty, weak accountability, and the risk of abuse of authority. This study uses a normative juridical method with a statute approach and a conceptual approach. The legal materials used consist of primary legal materials in the form of relevant laws and regulations, as well as secondary legal materials in the form of literature, journals, and expert legal opinions. The analysis is conducted descriptively and qualitatively to examine the conformity between the applicable legal rules and the practice of drafting and implementing BLU internal regulations. position as internal rules that are technical and operational in nature and cannot replace higher laws and regulations. The use of internal regulations as the main basis for PBJ has the potential to cause legal uncertainty, dualism of norms, and weaken the principle of good governance in state financial management. Therefore, regulatory harmonization between BLU internal policies and national laws and regulations is needed through the revision of LKPP Regulations, the formulation of national PBJ guidelines specifically for BLUs, and the strengthening of regulatory oversight mechanisms.